2003
DOI: 10.2105/ajph.93.6.955
|View full text |Cite
|
Sign up to set email alerts
|

Condom Availability Programs in Massachusetts High Schools: Relationships With Condom Use and Sexual Behavior

Abstract: The strategy of making condoms available, an indication of socioenvironmental support for condom use, may improve HIV prevention practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 51 publications
2
83
0
Order By: Relevance
“…71,72 Research has definitively found that giving teenagers increased access to birth control through advertising does not make them sexually active at a younger age. [73][74][75][76][77][78][79][80] American advertising also frequently uses female models who are anorectic in appearance and, thus, may contribute to the development of a distorted body selfimage and abnormal eating behaviors in young girls. 79,81,82 …”
Section: Sex In Advertisingmentioning
confidence: 99%
“…71,72 Research has definitively found that giving teenagers increased access to birth control through advertising does not make them sexually active at a younger age. [73][74][75][76][77][78][79][80] American advertising also frequently uses female models who are anorectic in appearance and, thus, may contribute to the development of a distorted body selfimage and abnormal eating behaviors in young girls. 79,81,82 …”
Section: Sex In Advertisingmentioning
confidence: 99%
“…[66][67][68] Eight peer-reviewed, controlled clinical trials have revealed that giving teenagers freer access to condoms does not increase their sexual activity or encourage virginal teenagers to begin having sex, but it does increase the use of condoms among those who are already sexually active. [69][70][71][72][73][74][75][76] Advertising condoms, birth control pills, and emergency contraception on TV and radio could further decrease the teen pregnancy rate. Yet, several networks refuse such advertisements.…”
Section: Contraceptive Advertisingmentioning
confidence: 99%
“…A number of studies have shown delay of onset of sexual initiation (e.g., Coyle, Kirby, Marin, Gómez, & Gregorish, 2004), whereas other programs have led to significant increases in condom use in populations including heterosexually active individuals (see Johnson, Carey, Marsh, Levin, & Scott-Sheldon, 2003;Neumann et al, 2002, for reviews). However, most of these interventions have been implemented in small-group (e.g., Belza et al, 2001), school (e.g., Blake et al, 2003;Gallant & Maticka-Tyndale, 2004), or individuallevel clinical settings (e.g., Morrison-Beedy & Lewis, 2001). Mass media campaigns, such as televised public service announcement (PSA) campaigns, have recently been shown to be highly effective in changing a variety of behaviors (Hornik, 2002;Noar, 2006) 2001).…”
mentioning
confidence: 99%